Analysis of Flexural Buckling Capacity of Stainless Steel Columns under Axial Compression - Yong Liang; Gapi Shu; Shaohua Li (Advances in Civil Engineering)
In order to provide a basis for the compilation of the bending buckling stability part of axially compressed columns in the technical code for stainless steel structures, the design methods and experimental research data of similar components are collected and compared. The results showed that there are some deficiencies in the current European code for the design of stainless steel structures and the American code for the design of cold-formed stainless steel structures. According to the collected test data of square tube, rectangular tube, circular tube, elliptical tube, welded H-shaped steel, and cold-formed C-shaped steel for 199 section columns and according to the influence of cold-formed effect and residual stress on the stability of axial compression members, the members are divided into three categories: A, B, and C according to the section form, in which the columns with cold-formed square, rectangular hollow section, and lipped C-section were included in A, columns with circular and oval hollow section were sorted into B, columns with welded H-section were separated into C, and the three categories of axial compression stability curves are expressed in the form of Perry formula. The comparison with the test data shows that the three kinds of curves can well estimate the stability bearing capacity of members, and the discreteness is small. The reliability of the proposed formula is analyzed, and the results show that its reliability index β meets the requirements of the GB 50068 standard.